PURIFICATION, ANTIOXIDANT ACTIVITY AND TOXICITY POLYSACCHARIDE FRACTION FROM RED ALGAE Gracilaria verrucosa - Muawanah Muawanah; Ahyar Ahmad; Hasnah Natsir (Hasanuddin University, 2017)
it contains polysaccharide compound. This research aims to isolate and examine the activity of antioxidant and toxicity of polysaccharide extract and fraction fromred algae Gracilariaverrucosa. The study was carried out by isolating the polysaccharide extract using aqueous 100 o C and methanol-ethanol precipitation .Purification of polysaccharide done by Column Chromatography DEAE-Cellulose and analysis polysaccharide concentration was using phenol-sulfuric acid. Antioxidant activity of crude extract and polysaccharide fraction was examined using DPPH method, and toxicity test was carried out using Brine Shrimp Lethality Test (BSLT). The research results reveals that the highest polysaccharide concentration was fraction 7 with value of 0,267 mg/mL, and the crude extract and fraction 4 have strongest antioxidant activity with IC50 values of 51,22 and 62,25 ppm, respectively. The result of BSLT assay showed that the crude extract and fraction 6 has a highest toxicity with LC50 values of 47,73and 58,48 ppm, therefore it is classified as toxic. The polysaccharide of crude extract and fraction 7 has a potential to be developed as an alternative antioxidant and antitumor agent. Identification with FT-IR shows the characteristic bands of agarocolloid.